1999
DOI: 10.1063/1.123093
|View full text |Cite
|
Sign up to set email alerts
|

Vertical self-alignment of quantum dots in superlattice

Abstract: Self-alignment of quantum dots separated by spacer layers is investigated by using a three-dimensional finite element method. We find that the morphology of the top islands is not just simply a reproduction of the buried islands. It is dependent on the arrangement of the buried islands, the interruption time, and the spacer layer thickness. If the buried islands are uniform and regular, with appropriate choice of their spacing and aspect ratio and with a thin spacer layer, there exists a regime in which the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…3,5,14 To explain this behavior, some authors have proposed that it is possible to obtain near equilibrium VAS QD structures only for highly elastic anisotropic materials. 3,12,15,16 In this sense, In͑Ga͒As islands on GaAs ͑001͒ have been observed to show surface alignment effects, 13,17,18 which give a clear indication of the anisotropy of the intrinsic surface stress tensor and the anisotropy of the bulk elastic modulus tensor. However, the molecular beam epitaxy ͑MBE͒ growth is governed by growth kinetics and this fact explains the lack of observations of anticorrelated behavior despite numerous studies of InGaAs multilayers.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…3,5,14 To explain this behavior, some authors have proposed that it is possible to obtain near equilibrium VAS QD structures only for highly elastic anisotropic materials. 3,12,15,16 In this sense, In͑Ga͒As islands on GaAs ͑001͒ have been observed to show surface alignment effects, 13,17,18 which give a clear indication of the anisotropy of the intrinsic surface stress tensor and the anisotropy of the bulk elastic modulus tensor. However, the molecular beam epitaxy ͑MBE͒ growth is governed by growth kinetics and this fact explains the lack of observations of anticorrelated behavior despite numerous studies of InGaAs multilayers.…”
mentioning
confidence: 95%
“…Following this reasoning, several authors have proposed that both VCS and VAS in self-assembled QD structures can be explained, taking into account the elastic anisotropy of the strain energy profile above a predeposited QD layer. 3,5,12,[14][15][16]20 The elastic anisotropy would change both the depth and the position of the energy minima with respect to elastically isotropic spacer layers where the energy minimum is always on the top of the buried QDs. Specifically, for GaAs͑001͒, there are four energy minima above a quantum dot which occur at ±23°from the vertical in the ͗110͘ directions, assuming the calculations of Holy et al 14 So, for the ϳ40 nm QD width observed in the bottom layer of sample A, four strain minima shifted ±10.5 nm from the vertical along the ͗110͘ directions would occur above these islands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Calculating the strain field by solving the anisotropic elastic theory equations by FEA using a compositional model of the studied nano-objects. This method has been proven to be one of the most efficient procedures to model the strain associated with these buried nanostructures [63][64][65][66]. Inputs for this compositional model are given by both spatially resolved EELS and aberration-corrected high-resolution Z-contrast images.…”
Section: Simulated and Experimental Determination Of Strain Map And Pmentioning
confidence: 99%
“…It has been shown that the dot size distribution and a vertical alignment need to be optimized among the growth conditions, including spacer thickness [17], material coverage [18], growth interruption [19], the number of periods of the multilayer [20,21], growth rate [22], post-growth annealing [23], and substrate miscut angle [24]. The physics behind them is the mechanical or elastic interaction of the islands via their strain fields.…”
Section: Introductionmentioning
confidence: 99%